External Pressure, Financial Target, Ineffective Monitoring and Rationalization on Financial Statement Fraud - Suwandi, Eko Darmawan (GOVERNORS, 2025)
Fraud is an act of deception or error committed by a person or entity who knows that the error can result in some disadvantageous benefits for the individual or entity or other party. This study aims to examine the factors that influence financial statement fraud. The dependent variable studied in this study is Financial Statement Fraud. The independent variables in this study consist of external pressure, financial targets, ineffective monitoring, and rationalization. This type of research is quantitative research that tests the influence between hypothesized variables through the presentation of numerical data. The data used in this study are secondary data sourced from the financial statements of Infrastructure, Utility and Transportation companies listed on the Indonesia Stock Exchange in 2021-2023. The determination of the sample in this study was determined using the purposive sampling method. The analysis technique used in the study is multiple linear regression analysis with the help of the SPSS program. The results of this study indicate that external pressure, financial targets, and ineffective monitoring partially have a positive and significant effect on Financial Statement Fraud. While the rationalization variable does not affect Financial Statement Fraud.